Understanding Management Marketing in Digitalization and Automation Times - Rudianto Rudianto; Misrofingah Misrofingah; Diansanto Prayoga; Juliana Juliana; Saipul Al Sukri; Kok Shiong Pong (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2022)
This study discusses some of the latest trends in business marketing governance in the era of Automation by emphasizing what is happening in business today compared to the past. This study is based on published data in the literature and internet-based data from various research articles, newspaper reports, and various website sites that actively discuss marketing trend issues in digital technology days. We understand that the business now and in the past still have the same goal, but what makes the difference is the marketing work system that used to be conventional but has now switched to digital, namely by optimizing internet searches that are based on marketing objectives, all marketing content and all information related to trading electronics became the main discussion to get an understanding of marketing management governance in the era of all-technology. We then studied the electronic data search method carefully and concluded that the point was that we got the findings as an answer to this royal question reported qualitatively. Based on the data exposure and discussion, we can inform the audience that today's business managers must understand how to influence consumers to win marketing by minimizing marketing costs so that companies get profits and their business continuity. Thus, it is hoped that this study will obtain results helpful in developing business marketing science in the digital era compared to traditional marketing techniques.